Method and Tools for Analyzing the Game Organization of Algerian First Division Football Teams (2008-2009 Season) - Salemi , Gaci; Bensalem, Salem (sports creativity, 2025)
This work aims to highlight certain aspects of game organization which, according to Mahler (1986) and Theodorescu (1977), inevitably determine the level of play in football. We focused on aspects of game organization in Algerian football. Our analysis centered particularly on playing systems and their implementation, on tactics and strategy, and finally on offensive and defensive organization, and transitions within the game. This study analyzes the game organization of seven Algerian Division 1 football teams from two perspectives: a qualitative perspective relating to the game organization itself, the systems and tactics employed, and a quantitative perspective focusing on ball recovery (number of balls recovered per zone). Essentially, our results highlight the difficulty of mastering the parameters of game organization, which depends on a rigorous and methodical approach to the training and development of young footballers. The current structure of our football does not allow trainers and coaches to adopt a methodical approach that meets the demands of modern football.